2009
DOI: 10.1111/j.1463-1326.2009.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical pathways of β‐cell failure in type 2 diabetes

Abstract: We review mechanisms of β-cell failure in type 2 diabetes. A wealth of information indicates that it is caused by impaired insulin secretion and decreased β-cell mass. Interestingly, there appears to be a link between these two mechanisms. The earliest reaction to peripheral insulin resistance is an increase in insulin production, owing primarily to increased secretion, and to a lesser extent to decreased clearance. Experimental animal models indicate that hyperinsulinaemia promotes an increase in β-cell mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…We have proposed that, as they rapidly respond to the β-cell’s nutritional state, FoxO are better positioned to translate the latter into an appropriate transcriptional programa than other transcription factors that don’t respond as nimbly to changes in glucose, lipid, and hormone levels. (Talchai et al, 2009) If the stress persists, FoxO levels drop through deacetylation-induced degradation that prevents the normal autoregulatory loop of FoxO expression (Kitamura et al, 2005; Talchai et al, 2012a). We now report that the loss of all three FoxO (likely through similar mechanisms) impairs the homeostatic MODY-related gene network, and activates Pparα-dependent lipid oxidative pathways, possibly resulting in increased supply of fatty acyl-derived acetyl-CoA for mitochondrial oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed that, as they rapidly respond to the β-cell’s nutritional state, FoxO are better positioned to translate the latter into an appropriate transcriptional programa than other transcription factors that don’t respond as nimbly to changes in glucose, lipid, and hormone levels. (Talchai et al, 2009) If the stress persists, FoxO levels drop through deacetylation-induced degradation that prevents the normal autoregulatory loop of FoxO expression (Kitamura et al, 2005; Talchai et al, 2012a). We now report that the loss of all three FoxO (likely through similar mechanisms) impairs the homeostatic MODY-related gene network, and activates Pparα-dependent lipid oxidative pathways, possibly resulting in increased supply of fatty acyl-derived acetyl-CoA for mitochondrial oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…While chronic exposure to high levels of glucose or free fatty acids is well known to have detrimental effects on beta cell function and survival [1,2,13], the mechanisms leading to initiation of the cell death program are complex, and the details remain to be clarified. In a previous study, we showed that stimulation of purinergic P2Y 13 receptors on beta cells activates apoptotic pathways [6].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated glucose and increased FFA have been shown to trigger pancreatic beta cell loss and dysfunction in type 2 diabetes [1], and increasing evidences demonstrate that longterm exposure to high glucose or FFA generates peripheral insulin resistance, both in vivo and in vitro resulting in pancreatic stress and increased susceptibility to beta cell apoptosis and, as a consequence, suppression of insulin secretion [2]. Although the overall picture is known, the detailed mechanisms underlying these effects are only partially understood.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of glucocorticoidinduced beta cell dysfunction is not well understood. Many observations point to a crucial role of the transcription factor forkhead box O1 (FOXO1) in beta cell failure [5]. However, the role of FOXO1 in the maintenance of beta cell function and appropriate beta cell mass is controversial [6].…”
Section: Introductionmentioning
confidence: 99%